Perilaku Anggota Dalam Pengambilan Keputusan Pembelian Produk Handphone Menggunakan Akad Murabahah Di Bmt Nu Singgahan Tuban - Naja, Elvina Karomatan; Sifa’, Moh Agus; Rikantasari, Shelvyna (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2024)
The aim of this research is to find out and analyze the behavior of members in making decisions to purchase mobile phone products using a murabahah contract at BMT NU Singgahan Tuban. This research uses descriptive qualitative research methods with qualitative descriptive techniques using interview techniques with BMT and its members, both structured and unstructured. In structured interviews, researchers first create and organize questions to interview informants, while for unstructured interviews, researchers will explore the questions in depth. when there is missing data and the question is asked via WhatsApp, observe. The results of this research show that there are three psychological factors that influence BMT NU Singgahan Tuban members in making decisions to purchase mobile phone products using a murabahah contract, namely motivation factors, perception factors, and belief and attitude factors. Murabaha financing members purchase the first four processes in making purchasing decisions, namely recognizing needs, searching for information, evaluating alternatives, and purchasing decisions.